(untitled) (FULafia Journal of Science and Technology, 2020)
The study examines the effect of power sector reform on energy supply in Nigeria using Akure 33kV distribution Network as a case study. The study employed Average Service Availability Index (ASAI), System’s Average Interruption Duration Index (SAIDI), Network’s failure rate and the overall system reliability. The analysis was divided as pre and post privatization; (2010-2012 and (2013-2015), respectively. The result showed decrease in the service availability rate by1%, and 7.6% increase in the average interruption duration index from 2010 to 2015. The network’s failure rate increased by 8% whiles the system’s reliability index decreased by 1.1%.